2015
DOI: 10.1093/jxb/erv240
|View full text |Cite
|
Sign up to set email alerts
|

A novel NAP member GhNAP is involved in leaf senescence inGossypium hirsutum

Abstract: HighlightGhNAP could regulate leaf senescence via the ABA-mediated pathways and is related to the yield and quality of cotton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 58 publications
(79 reference statements)
2
62
2
Order By: Relevance
“…GhNAC12 and GhNAP are reported to promote senescence and yield improvement (Zhao et al, 2015;Fan et al, 2015). Our study points out to one of GhNACs, GhNAC18, which, unlike others previously reported, is downregulated during leaf senescence and could be involved in cotton stress responses.…”
Section: Characterization and Cloning Of Ghnac18contrasting
confidence: 37%
See 1 more Smart Citation
“…GhNAC12 and GhNAP are reported to promote senescence and yield improvement (Zhao et al, 2015;Fan et al, 2015). Our study points out to one of GhNACs, GhNAC18, which, unlike others previously reported, is downregulated during leaf senescence and could be involved in cotton stress responses.…”
Section: Characterization and Cloning Of Ghnac18contrasting
confidence: 37%
“…Biotic attacks such as infectious pathogens also complicate the sessile habit of plants. In this regard, plants adapt to these dynamic conditions by evoking responses at physiological, biochemical and molecular levels (Nakashima et al, 2011;Fan et al, 2015) including regulation of genes enhancing survivability (Nuruzzaman et al, 2013). The immune response in plants is triggered by pathogen infection that is characterized by activation of multiple defense responses including expression of defenserelated genes, regulated by different types of transcription factors (TFs).…”
Section: Introductionmentioning
confidence: 99%
“…Regulates leaf senescence via the ABA mediated pathway [128] 20 GhXND1/XYLEM NAC DOMAIN 1 (Gossypium hirsutum)…”
Section: Full Length and C-terminal Nucleusmentioning
confidence: 99%
“…For example, AtORE1, OsNAC2 and SIORE2 are members of the ORE1 subgroup of the NAC gene family, which regulate leaf senescence (Kim et al, 2009;Mao et al, 2017;Lira et al, 2017). AtNAP, GhNAP, OsNAP, SiNAP and BeNAP belong to the NAP subgroup of the NAC gene family, and all of which also regulate senescence (Guo & Gan, 2006;Chen et al, 2011;Liang et al, 2014;Fan et al, 2015;Ren et al, 2017a). Moreover, Most NAC genes regulate plant senescence by participating in the regulatory pathways of senescence-related hormones and/or stress response, such as abscisic acid (ABA), methyl jasmonate (MeJA), ethylene, salicylic acid (SA), drought, salt stress, dark and so on.…”
Section: Introductionmentioning
confidence: 99%
“…(B) Leaves detached from plants in (A). G1-G3, three groups of leaves divided according to the senescence status and the method ofFan et al (2015). G1, the first to the sixth leaves which were dry.…”
mentioning
confidence: 99%